Perspektif Otonomi Daerah Dalam Desentralisasi - Supriatna, Tjahya (Jurnal Wahana Bina Pemerintahan, 2016)
The purpose of this study was to describe the laying of regional autonomy in local governance based on the theory of decentralizaion and regional autonomy, Qualitative approach is used to answer the questions proposed in this study. The result of this study shows that the implementation of the policy of decentralizaion and regional autonomu have relevance to the theory of Symmetric an A-symmetric Decentralizaion. Laying of regional autonomy in the Moderate Model composed of first, the Provincial Regions with special authority or limited authonomy and administrative region. Second, The Distric/City regions as fully authonomy.